The practice of platelet transfusion prior to central venous catheterization in presence of coagulopathy: a national survey among clinicians. Issue 4 (5th March 2017) - van de Weerdt, E. K.; Peters, A. L.; Goudswaard, E. J.; Binnekade, J. M.; van Lienden, K. P.; Biemond, B. J.; Vlaar, A. P. J.
Abstract : Background: Correction of coagulopathy prior to central venous catheter (CVC) placement is advocated by guidelines, while retrospective studies support restrictive use of transfusion products. Study Design and Methods: We conducted a mixed vignette and questionnaire web survey to investigate current practice and preferences for CVC placement. Clinical vignettes were used to quantify the tendency to administer platelet concentrate. A positive ß‐coefficient is in favour of administering platelet concentrate. Results: Ninety‐seven physicians answered the survey questions (36 critical care physicians, 14 haematologists, 20 radiologists and 27 anaesthesiologist). Eighty‐six physicians subsequently completed the clinical vignettes (response rate 71%). Preferences in favour of correcting thrombocytopenia prior CVC placement were platelet counts of 10 × 10 9 /L and 20 × 10 9 /L (ß = 3·9; ß = 3·2, respectively), the subclavian insertion site (ß = 0·8). An elevated INR (INR = 3; ß = 0·6) and an elevated aPTT (aPTT = 60 s; ß = 0·4) showed a positive trend towards platelet transfusion. Platelet transfusion was less likely in an emergency setting (ß = −0·4). Reported transfusion thresholds for CVC placement varied from <10 × 10 9 /L to 80 × 10 9 /L for platelet count, from 1·0 to 10·0 for INR and from 25 s to 150 s for aPTT. Implementation of ultrasound guidance as standard practice was limited. Conclusion: Current transfusion practice prior to CVC placement is highly variable. Physicians adjust the decision to correct coagulopathy prior CVC placement based on clinical parameters, insertion site and technique applied.